2015
DOI: 10.4238/2015.july.31.23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bone marrow mesenchymal stem cells on the TGF-β1/Smad signaling pathway of hepatic stellate

Abstract: ABSTRACT. This study investigated the effect of bone marrow mesenchymal stem cells (BMCs) on the transforming growth factor-β1 (TGF-b1)-induced activation of the Smad signaling pathway in rat hepatic stellate cells (HSCs). There were four experimental groups: 1) a blank control group, 2) a TGF-b1 treatment group, 3) an MSCcombined group, and 4) an induced MSC-combined group. Isolation and culture of rat liver HSCs in vitro and the proliferation of HSCs in each group were detected by MTT method. The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…28 However, MSC-mediated paracrine signaling stimulated cell proliferation and suppressed myofibroblast differentiation in skin fibroblasts, keratinocytes, hepatic stellate cells, and glomerular fibroblasts. 29-32 These previous reports concur with data from the current study.…”
Section: Discussionsupporting
confidence: 91%
“…28 However, MSC-mediated paracrine signaling stimulated cell proliferation and suppressed myofibroblast differentiation in skin fibroblasts, keratinocytes, hepatic stellate cells, and glomerular fibroblasts. 29-32 These previous reports concur with data from the current study.…”
Section: Discussionsupporting
confidence: 91%
“…TGF-b1 is involved in EMT processes and favours the formation of PF. 23 Hiwatashi et al 24,25 Previous study showed that peritoneal mesothelial cells could excrete various cytokines and growth factors, 27 and intraperitoneal transplantation of mesothelial cells was an effective way of attenuating peritoneal damage. 28 Foley-Comer et al 29 found that cultured and lavage-derived mesothelial cells had the ability to attach to the injured serosal surface, proliferate and became incorporated into the reconstituted mesothelium.…”
Section: Tgf-b1-induced Emt In Rpmcsmentioning
confidence: 99%
“…Multiple signaling pathways or channels have been confirmed to participate in the regulatory mechanism of hBM-MSCs on HSC activation [ 35 , 36 ], and our study may provide a new clue and possibility for explaining the protective effect of hBM-MSCs on liver fibrosis. The antifibrotic effects of the hBM-MSCs were also investigated by carbon tetrachloride- (CCl 4 -) induced liver fibrotic mouse model via the liver portal vein; the hBM-MSCs recover liver function markers at 21 days after transplantation.…”
Section: Discussionmentioning
confidence: 73%